2019
DOI: 10.1097/01.asw.0000569120.36663.34
|View full text |Cite
|
Sign up to set email alerts
|

Is Negative-Pressure Wound Therapy a “Bridge to Reconstruction” for Poststernotomy Mediastinitis? A Systematic Review

Abstract: OBJECTIVE: To assess the efficacy of negative-pressure wound therapy (NPWT) in preparing sternal wounds for flap reconstruction. METHODS: Investigators searched standard research databases with terms including “post-sternotomy mediastinitis,” “deep sternal wound infection,” “negative pressure wound therapy,” “vacuum assisted closure,” and “VAC.” Of 434 reports, 14 studies described patients diagnosed with poststernotomy mediastinitis who underwent NPWT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Although some advocate wound vacuumassisted closure use as initial therapy or a bridge between débridement and definitive closure, they do not factor in the timing from wound development to reconstruction. [10][11][12] Song et al demonstrated the safety and utility of such an approach in a cohort of over 100 patients, finding that up to one-third of patients did not require definitive closure after débridement and vacuum-assisted closure device placement. 13,14 However, a similar number (36 percent) of patients in that series had a sterile or superficial wound.…”
Section: Discussionmentioning
confidence: 99%
“…Although some advocate wound vacuumassisted closure use as initial therapy or a bridge between débridement and definitive closure, they do not factor in the timing from wound development to reconstruction. [10][11][12] Song et al demonstrated the safety and utility of such an approach in a cohort of over 100 patients, finding that up to one-third of patients did not require definitive closure after débridement and vacuum-assisted closure device placement. 13,14 However, a similar number (36 percent) of patients in that series had a sterile or superficial wound.…”
Section: Discussionmentioning
confidence: 99%